Step-by-step explanation:
x=y³/z
(y³/z) to the power of a = y to the power of b
[tex] {y}^{3a} \div {z}^{a} = {y}^{b} [/tex]
[tex] {y}^{3} \div z = {y}^{b \div a} [/tex]
[tex] {y}^{3 \div b} \div {z}^{1 \div b} = {y}^{1 \div a} [/tex]
[tex] {y}^{3 \div b} = {y}^{1 \div a} {z}^{1 \div b} [/tex]
[tex] {y}^{b} = {z}^{c} [/tex]
[tex]z = {y}^{b \div c} [/tex]
[tex] {y}^{3 \div b} = {y}^{1 \div a} \times ({y^{b \div c} })^{1 \div b} [/tex]
[tex] {y}^{3 \div b} = {y}^{1 \div a} \times {y}^{1 \div c} [/tex]
as b/c × 1/b = 1/c
and so we see based on the exponents that
3/b = 1/a + 1/c